Carrying capacity of reinforced concrete columns, reinforced with collars from fiber-reinforced plastics, with little dynamic loads - Bespaev Aliy; Kuralov Ulan (E3S Web of Conferences, 2023)
The article presents the results of experimental studies of the carrier ability, longitudinal and transverse deformations of reinforced concrete columns, reinforced clips made of fiber-reinforced plastics, with a few repeated loads. Dependences of residual strength after cyclic compressive forces are obtained. Are given suggestions for acceptable deformation values of fiber-reinforced plastics, as well as proposals for calculation and design.